2021
DOI: 10.3390/ijms22126453
|View full text |Cite
|
Sign up to set email alerts
|

The Divergent Immunomodulatory Effects of Short Chain Fatty Acids and Medium Chain Fatty Acids

Abstract: Fatty acids are derived from diet and fermentative processes by the intestinal flora. Two to five carbon chain fatty acids, termed short chain fatty acids (SCFA) are increasingly recognized to play a role in intestinal homeostasis. However, the characteristics of slightly longer 6 to 10 carbon, medium chain fatty acids (MCFA), derived primarily from diet, are less understood. Here, we demonstrated that SCFA and MCFA have divergent immunomodulatory propensities. SCFA down-attenuated host pro-inflammatory IL-1β,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 42 publications
3
26
0
Order By: Relevance
“…TLR4, existing in the form of a homodimer and signaling through MyD88, is thought to exhibit conservatism evolutionarily in its sentinel role to regulate essential bodily function. SCFAs in the host intestine are in line with the conservative signal receptor characteristic of TLR4, inhibiting large-scale inflammation response in response to local TLR4. , To investigate whether TLR4/MyD88/NF-κB mediates the anti-inflammatory effect of SCFAs, the expression levels of pathway proteins and downstream cytokines were assessed. After treatment with allicin, protein levels of the TLR4/MyD88/NF-κB pathway and TNF-α, IL-1β, IL-6, and IL-18 levels decreased dramatically, while the IL-10 level increased, indicating that intestinal inflammation was evidently suppressed.…”
Section: Discussionmentioning
confidence: 99%
“…TLR4, existing in the form of a homodimer and signaling through MyD88, is thought to exhibit conservatism evolutionarily in its sentinel role to regulate essential bodily function. SCFAs in the host intestine are in line with the conservative signal receptor characteristic of TLR4, inhibiting large-scale inflammation response in response to local TLR4. , To investigate whether TLR4/MyD88/NF-κB mediates the anti-inflammatory effect of SCFAs, the expression levels of pathway proteins and downstream cytokines were assessed. After treatment with allicin, protein levels of the TLR4/MyD88/NF-κB pathway and TNF-α, IL-1β, IL-6, and IL-18 levels decreased dramatically, while the IL-10 level increased, indicating that intestinal inflammation was evidently suppressed.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with IBD, butyrate inhibits the TLR2-mediated release of inflammatory factors [ 74 , 75 ]. Butyric acid also reduces adapter protein expression level [ 76 ]. In addition, increased level of TLR4 signaling also reduces the abundance of SCFA-producing flora in the gut, which is highly relevant to the development of IBD [ 75 ].…”
Section: Scfas Regulate the Recognition Of Innate Immune Sensors To I...mentioning
confidence: 99%
“…found that caprylic acid (C8:0) downregulated the serum levels of interleukin-1β (IL-1β) and interferon γ (IFNγ) and increased the abundance of Lachnoclostridium , Roseburia , and Prevotella_9 , activating GPR43 and improving intestinal permeability ( 113 ). Capric acid (C10:0) can upregulate GPR84 and peroxisome proliferator-activated receptor γ (PPARγ) ( 114 ). Dodecanoic acid (C12:0), also known as lauric acid, can improve insulin sensitivity ( 100 ).…”
Section: The Relationship Between Pediatric Overweight/obesity and Gu...mentioning
confidence: 99%